Trends in street tree species selection: developing a theoretical model - Buang, Sabarudin; Maulan, Suhardi; Tahir, Osman; Simangunsong, Nur Intan (e-International Publishing House, 2024)
This study develops a framework for urban tree species selection by analyzing trends in 45 recent articles (2019–2024) with keywords “street,” “tree species,” and “selection.” The thematic analysis identifies five themes: species diversity, ecosystem services, climate adaptability, public perception, and management challenges. Addressing gaps in current trends, this research integrates tree morphology in existing models and employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to validate criteria for resilience, social acceptance, and economic viability. The resulting model offers a flexible, context-sensitive approach to sustainable urban forestry, enhancing ecological and social benefits across diverse urban environments.